Toddlers Assert and Acknowledge Ownership Rights. Issue 2 (10th November 2014) - Ross, Hildy; Friedman, Ori; Field, Aimee
Abstract Two studies compared toddler owners and non‐owners of toys. Children of 24 and 30 months were supplied with toys and told that they were owners. In play with friends, owners were more likely than non‐owners to maintain possession, claim toys verbally ('mine'), and non‐verbally, by attempting to regain their own toys in their friends' possession. Children communicated their ownership early in each episode and in preference to other information about the toys. Toddlers in both studies identified toys belonging to their friends and acknowledged their friends' ownership with possessive statements ('yours'), and in Study 2, recognized the relationship between owners and their property by offering toys that their friends owned. In these ways, toddlers' actions were consistent with accepted ownership rights.